THE EFFECT OF POWER TRANSFER AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE MEDIATED BY GOOD GOVERNMENT GOVERNANCE IN REGIONAL GOVERNMENT AGENCY (OPD) OF RIAU PROVINCE - Ginda Burnama; Zulfadil Zulfadil; Susi Hendriani; Samsir Samsir (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the direct and indirect influence of Transfer of power and organizational culture on employee performance, mediated by good government governance. This research was conducted at the Regional government agency (OPD) of Riau Province. A quantitative approach was used. The population in this study was 150 employees of the Regional government agency (OPD) of Riau Province. The sample was a portion of the population with relatively similar characteristics and could be considered representative of the population using the Slovin technique, thus obtaining the sample using the Slovin formula. In distributing the questionnaire, the sampling method in this study used the Stratified Random Sampling technique. The results of this study indicate that transfer of power and organizational culture have a significant influence on good government governance. Furthermore, transfer of power, organizational culture, and good government governance have a significant influence on employee performance. Furthermore, good government governance can mediate the influence of transfer of power and organizational culture on performance.